PENGARUH PDRB PERIKANAN TERHADAP PENGHIDUPAN BERKELANJUTAN DI SULAWESI - Moki, Nur Intan; Baruwadi, Mahludin H; Hippy, Mohammad Zubair (Chanos Chanos, 2024)
The agricultural industry and fisheries subsector can contribute to improving the economy in Indonesia, specially on the island of Sulawesi. This research aims to analyze trends in agricultural GRDP in the fisheries subsector and its influence on the sustainable livelihood of the community. The method applied in this research is descriptive analysis and panel data regression analysis which is carried out by testing data normality using the e-views 9 testing tool. Data collection techniques include observation, documentation, and literature study. The results of this research show 1). The GDP trend in the agricultural and fisheries sectors on Sulawesi Island shows a positive increase which supports the region's economy. Although both sectors experienced fluctuations due to the COVID-19 pandemic in 2020, the fisheries sector recovered significantly in 2021 with a growth rate of 6.23%, which was driven by the recovery of export markets and government support, while the agricultural industry remains stable thanks to modernization and infrastructure improvements, 2). Its influence on community welfare, as measured through life expectancy (AHH), also shows positive results; around 73.42% of the variation in AHH in Sulawesi is influenced by changes in GRDP in the fisheries sector, which reflects that the increase in this sector is in line with improvements in the quality of life of the community. Both of these results show positive results, so increasing the contribution of agricultural GDP to the fisheries subsector plays an important role in community welfare.Sektor pertanian dan subsektor perikanan mampu memberikan kontribusi dalam peningkatan perekonomian di Indonesia khususnya Pulau Sulawesi. Penelitian ini bertujuan menganalisis trend PDRB pertanian subsektor perikanan dan pengaruhnya terhadap penghidupan keberlanjutan masyarakat. Metode yang di aplikasikan dalam penelitian ini yakni analisis deskriptif dan analisis regresi panel data yang dilakukan dengan uji normalitas data menggunakan alat pengujian e-views 9. Teknik pengumpulan data menggunakan teknik observasi, dokumentasi dan studi pustaka. Hasil dari penelitian ini menunjukkan 1). Trend PDRB sektor pertanian dan perikanan di Pulau Sulawesi menunjukkan peningkatan positif yang mendukung perekonomian wilayah ini. Walaupun kedua sektor mengalami fluktuasi akibat pandemi COVID-19 pada tahun 2020, sektor perikanan pulih secara signifikan pada 2021 dengan tingkat pertumbuhan 6,23%, yang didorong oleh pemulihan pasar ekspor dan dukungan pemerintah, sementara sektor pertanian tetap stabil berkat modernisasi dan perbaikan infrastruktur,  2). Pengaruhnya terhadap kesejahteraan masyarakat, yang diukur melalui penghidupan berkelanjutan (AHH) juga menunjukkan hasil positif; sekitar 73,42% variasi AHH di Sulawesi dipengaruhi oleh perubahan PDRB sektor perikanan, yang mencerminkan bahwa peningkatan sektor ini sejalan dengan peningkatan kualitas hidup masyarakat. Dengan demikian, optimalisasi subsektor perikanan dapat meningkatkan kesejahteraan masyarakat secara berkelanjutan